Case report: Histological findings of peri-appendicitis in three children with SARS-CoV-2 – related multisystem inflammatory syndrome: A mark for systemic inflammation? - Fabi, Marianna; Vasuri, Francesco; Guida, Fiorentina; Rocca, Alessandro; Lima, Mario; D’Errico, Antonietta; Lanari, Marcello (Frontiers in Pediatrics, 2022)
Background Multisystem inflammatory syndrome in children (MIS-C) is a rare but serious condition potentially developing after SARS-CoV-2 infection in children. Gastrointestinal manifestation in MIS-C can mimic acute abdomen, potentially leading to unnecessary surgical treatment. Immune-mediated mechanisms seem to be determining in its pathogenesis and histological studies can help to shed light on this aspect. We describe three cases of children diagnosed with MIS-C that underwent to appendectomy. Methods We retrospectively collected the clinical features and histological findings of three previously healthy children who underwent appendectomy for clinical suspicion of acute appendicitis, but were later diagnosed with MIS-C. Findings The three children presented with prominent abdominal manifestations and fever leading to the suspicion of acute abdomen. Histological findings showed transmural and perivascular inflammation. Notably, CD68+ macrophages were predominant in the child with milder abdominal symptoms without cardiac injury, while CD3+ lymphocytes in the patient presenting with more severe abdominal pain and cardiovascular involvement at admission. Interpretation Gastrointestinal symptoms of children with MIS-C improve after proper immunomodulatory therapy, conversely showing inadequate response to surgical appendectomy. Histological findings revealed different inflammatory cell infiltration that primarily involved perivisceral fat and vessels, and subsequently mucosal tissue, in contrast to other forms of acute appendicitis. Our findings suggest that this kind of peri-appendicitis in MIS-C could represent a focal sign of systemic inflammation, with different histological patterns compared to other forms of acute appendicitis.